New deep-sea Atlantic and Antarctic species of Abyssorchomene De Broyer, 1984 (Amphipoda, Lysianassoidea, Uristidae) with a redescription of A. abyssorum (Stebbing, 1888) - Hendrycks, Ed A.; De Broyer, Claude (European Journal of Taxonomy, 2022)
During the Census of Marine Life Polarstern ANDEEP I-III and Meteor M79/1 DIVA-3 expeditions, autonomous baited trap systems were employed to sample the mobile, necrophagous amphipods from abyssal depths. Within DIVA-3 (July 10–August 26 2009), a free-fall baited trap was used successfully at three stations in the southwest Atlantic, once in the Argentine Basin and twice in the Brazilian Basin. A total of twenty-one stations were sampled by baited traps during the ANDEEP I-III (2002, 2005) cruises in the Southern Ocean. Trap sets recovered large numbers of scavenging lysianassoid and alicelloid amphipods, including specimens of the widespread and commonly considered cosmopolitan uristid species Abyssorchomene abyssorum (Stebbing, 1888). During examinations of these and other North Atlantic collections of A. abyssorum, two similar new species A. patriciae sp. nov. and A. shannonae sp. nov. were discovered. Important morphological characters which differentiate the two new species from their congeners are found in the shape of the head lobe, coxa 1, gnathopod 2, coxa 5, pereopod 7 basis and uropod 3 rami length. The new species are fully figured and an identification key is provided. Abyssorchomene abyssorum is redescribed and for the first time, the female is fully described and illustrated from new material. The Southern Ocean endemic A. scotianensis (Andres, 1983) is also described and illustrated from new collections to complement the original description.